Arrangements of Hepatobiliary Cystadenoma Complicated With Congenital Choledochal Cyst. Issue 3 (January 2015) - Li, En-Liang; Shi, Shi-Dai; Huang, Yong; Wu, Lin-Quan; Merrett., Neil
<x xml:space="preserve">Abstract</x> Abstract Hepatobiliary cystadenoma complication with congenital choledochal cyst is extremely rare and has never been reported in literatures so far. The aim of the study was to investigate the disease arrangements by analyzing the case and performing a systematic review of the literature. This case report documents the details and clear patterns of the patient. A 65-year-old woman with fever (39.2°C), nausea, vomiting, and chronic hepatitis B imaging demonstrated a left hepatic multilocular cystic mass and cystic dilated common bile duct. A regular left hemihepatectomy was performed with resection of the entire tumor and choledochal cyst. The surgical margins were negative and a final diagnosis of hepatobiliary cystadenoma complicated with congenital choledochal cyst was established. The patient had an uneventful postoperative recovery and liver function returned to normal levels. Main lessons learned from this case are: the awareness should be raised about the disease to avoid misdiagnosis; preoperative ultrasonography, computed tomography, magnetic resonance imaging, and magnetic resonance cholangiopancreatography play an important role in detecting the lesion; the scope and timing of the surgery should be determined, which provide the chance of cure to complete resection of the tumor.